PENGENALAN BRANDING DAN DIGITAL MARKETING PRODUK OLAHAN IKAN PUPU’ PADA INDUSTRI RUMAH TANGGA DI LINGKUNGAN PARAPPE KECAMATAN BANGGAE TIMUR KABUPATEN MAJENE - Madjid, Irma Yulia; Fitriah, Reski; Salsabila, Chairunnisa; Aswad, Muhammad (Jurnal Abdi Insani, 2024)
Micro, Small and Medium Enterprises (MSMEs) are currently increasing in number in Indonesia. MSMEs are often found in the fisheries and marine products industry. As technology develops, MSMEs are also required to be able to use and utilize existing technology, especially in terms of marketing. Branding and digital marketing are new things for small businesses. The Pupu' fish processing business which is quite well known in Majene Regency is one of the household scale processing industry businesses. Production and marketing which are still carried out traditionally make this business unable to compete with MSMEs with the same type of fishery product processing business which utilizes digital technology in terms of marketing. The aim of this community service activity is so that the Pupu' fish processing business group is able to produce processed fish products that are hygienic and competitive with other products, as well as being able to market them digitally. This activity is carried out by providing material related to branding and digital marketing directly to industry players and their workers, providing ways to market products through digital marketing by changing mindsets and knowledge related to digital marketing communications, improving skills in communicating brands and products through media. digital, and carry out training on labeling packaging for household industrial products. From this court activity, the result was that business actors already had social media accounts which would become a forum for carrying out promotions through social media. Products that were initially only marketed by consumers going directly to the location where the pupu' product was made are now being marketed via social media by creating attractive packaging and labeling it with the name of the production. This is expected to increase the income of business actors and reach further markets.  The most important thing about this service activity is changing a new mindset to become an entrepreneur by having progressive changes based on digital technology.